Challenges Facing Viral Hepatitis C Elimination in Lebanon - Nour Ayoub; Taha Hatab; Abdul Rahman Bizri (Pathogens, 2023)
Hepatitis C is a hepatotropic virus that causes progressive liver inflammation, eventually leading to cirrhosis and hepatocellular carcinoma if left untreated. All infected patients can achieve a cure if treated early. Unfortunately, many patients remain asymptomatic and tend to present late with hepatic complications. Given the economic and health burdens of chronic hepatitis C infection, the World Health Organization (WHO) has proposed a strategy to eliminate hepatitis C by 2030. This article describes the epidemiology of hepatitis C in Lebanon and highlights the challenges hindering its elimination. An extensive search was conducted using PubMed, Medline, Cochrane, and the Lebanese Ministry of Public Health–Epidemiologic Surveillance Unit website. Obtained data were analyzed and discussed in light of the current WHO recommendations. It was found that Lebanon has a low prevalence of hepatitis C. Incidence is higher among males and Mount Lebanon residents. A wide variety of hepatitis C genotypes exists among various risk groups, with genotype 1 being the most predominant. In Lebanon, many barriers prevent successful hepatitis C elimination, including the absence of a comprehensive screening policy, stigma, neglect among high-risk groups, economic collapse, and a lack of proper care and surveillance among the refugees. Appropriate screening schemes and early linkage to care among the general and high-risk populations are essential for successful hepatitis C elimination in Lebanon.